1991
DOI: 10.1001/jama.1991.03470230047029
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Endarterectomy and Prevention of Cerebral Ischemia in Symptomatic Carotid Stenosis

Abstract: For a selected cohort of men with symptoms of cerebral or retinal ischemia in the distribution of a high-grade internal carotid artery stenosis, carotid endarterectomy can effectively reduce the risk of subsequent ipsilateral cerebral ischemia. The risk of cerebral ischemia in this subgroup of patients is considerably higher than previously estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
157
0
6

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 799 publications
(170 citation statements)
references
References 22 publications
5
157
0
6
Order By: Relevance
“…[1][2][3]18 The degree of stenosis is also the basis for surgical intervention in asymptomatic patients 19 and in endovascular treatment for carotid disease. 20 The premise that various pathologic stages in the evolution of carotid atheroma are predictive of clinical events remains to be convincingly proved in patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3]18 The degree of stenosis is also the basis for surgical intervention in asymptomatic patients 19 and in endovascular treatment for carotid disease. 20 The premise that various pathologic stages in the evolution of carotid atheroma are predictive of clinical events remains to be convincingly proved in patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines are derived from strong clinical trial data that examined primarily the longterm risk of stroke. [1][2][3] Although degree of stenosis is a good surrogate marker for atherosclerotic vascular disease, based on the plausible assumption that vessel narrowing is caused by plaque accumulating in the lumen of the artery, there may be other factors that could potentially predict clinical behavior of atherosclerotic plaques. Plaque characteristics such as lipidrich core, fibrous cap thickness, and intraplaque hemorrhage have been demonstrated on noninvasive imaging modalities such as sonography [4][5][6] and MR imaging, [7][8][9][10][11][12][13][14] and it is suggested that these ancillary features, taken in conjunction with the degree of stenosis, may be important predictors of immediate and long-term stroke risk.…”
mentioning
confidence: 99%
“…Transient ischemic attack patients generally fall into three treatment categories: (1) those identified with modifiable risk factors, including hypertension, diabetes mellitus, hyperlipidemia, atrial fibrillation, and cigarette smoking; (2) individuals who have greater than 70% carotid stenosis and are candidates for neurointerventional or surgical procedures such as stenting or endarterectomy (Barnett et al, 1998;Mayberg et al, 1991); and (3) those who fall into neither of these categories and are released with a standard course of antiplatelet therapy.…”
Section: Transient Ischemic Attacks Recapitulate the Findings Of Neurmentioning
confidence: 99%
“…carotid endarterectomy) has become the most powerful form of stroke prevention for individuals with symptomatic and asymptomatic high-grade carotid artery stenosis (Figure 2). Indeed, the 3 year risk of stroke and death in individuals is reduced by half in individuals who received endarterectomy compared with aspirin therapy alone (Mayberg et al, 1991). An alternative strategy for restoring blood flow to the brain is percutaneous transluminal angioplasty with stent (or 'carotid stenting'), which is becoming a desirable alternative to endarterectomy particularly in patients with restenosis after endarterectomy, those who have serious angina, chronic obstructive pulmonary disease, heart failure or other circumstances where anesthesia and surgery pose high risks (Yadav et al, 2004).…”
Section: Surgical Intervention After Transient Ischemic Attack: a Primentioning
confidence: 99%
“…24 Recommendations for surgical and endovascular treatment in LvD patients extracranial carotid disease Carotid endarterectomy (CEA) is recommended for patients with recent TIA or ischemic stroke and severe (70%) ipsilateral internal carotid artery stenosis. 10,[45][46][47] CEA is also effective in patients with symptomatic ipsilateral moderate (50%-69%) stenosis of the internal carotid artery, but the benefit is less. 10,48 Based on one clinical trial, balloon angioplasty and stenting of the internal carotid artery may be considered for "high risk" patients with symptomatic, severe stenosis of the internal carotid artery.…”
Section: -41mentioning
confidence: 99%